Comprehensive profiling of lncRNAs in the immune response of largemouth bass to Nocardia Seriolae infection - Xiaona Fu; Longsheng Zhang; Keqi Li; Zhigang Liu; Jikui Wu; Junling Zhang (Comparative Immunology Reports)
Long noncoding RNAs (lncRNAs) are crucial regulators of various biological processes. However, it remains unclear how lncRNAs can be involved in the immune response to Nocardia seriolae invasion in largemouth bass (Micropterus salmoides). Here we leveraged the whole transcriptome RNA-seq technique to screen lncRNAs associated with the head kidney infected with Nocardia seriolae. A total of 5,661 lncRNAs were identified, comprising 2,427 known lncRNAs and 3,234 novel lncRNAs. Among these, 531 lncRNAs were found to be differentially expressed, with 213 showing increased expression and 318 showing reduced expression. In these differentially expressed lncRNAs, 176 lncRNAs may have cis-regulatory relationships with 243 protein-coding genes. For example, MSTRG.17818.1, MSTRG.10160.1 target mapk1 and rela, respectively, thereby regulating gene expression. We then exploited Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) to analyze the enrichment of target genes of lncRNAs. These target genes were found to be significantly enriched in immune signaling pathways, including RIG-I-like receptor signaling and Toll-like receptor signaling. Furthermore, we harnessed a total of 12 mRNAs, 33 miRNAs, and 167 lncRNAs to construct two lncRNA-miRNA-mRNA network maps. CeRNA maps revealed that some lncRNAs can competitively bind to the same miRNA and affect the expression of immune-related genes. For instance, MSTRG.13668.1 and MSTRG.5180.1 can simultaneously bind to mir-155–5p to increase irak4 expression. These findings suggest that lncRNAs may participate in the immune response process of infected largemouth bass with Nocardia seriolae. Overall, this work presents a thorough lncRNAs expression profile of Nocardia seriolae-infected largemouth bass and offers insights into the ceRNA regulatory processes that influence fish's immune response to bacterial infections.